The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/0892705718805535
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on mechanical properties of pineapple leaf–based short fiber–reinforced polymer composite from selected Indian (northeastern part) cultivars

Abstract: The natural fiber–reinforced polymer composites gaining substantial importance in recent years due to their unique properties compared to synthetic composites. In India (especially northeastern part), cultivars and industries mostly focus on pineapple fruits, leaving leaf to mainly compost or burn and decay as an agro waste. In this article, pineapple leaf–based (variety type Kew or Giant Kew from Silchar, Assam, India) short fiber–reinforced polymer composites as a function of fiber composition and composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 22 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…Various structures from fibers to complicated structures have been designed to provide the desired properties and to reduce the overall cost of composite without compromising the final performance. 25,27 The fibers can be found in a variety of forms including short fibers, 28 continuous fibers, 29 whiskers, 30 nanofibers, 31 hollow fibers 32 or looped form fibers. 33 Interface is the region between the polymeric matrix and the discontinuous phase (fibers or fillers) and is considered to be the predominant factor that strongly affect the FRPCs performance.…”
Section: Frpcs and Componentsmentioning
confidence: 99%
“…Various structures from fibers to complicated structures have been designed to provide the desired properties and to reduce the overall cost of composite without compromising the final performance. 25,27 The fibers can be found in a variety of forms including short fibers, 28 continuous fibers, 29 whiskers, 30 nanofibers, 31 hollow fibers 32 or looped form fibers. 33 Interface is the region between the polymeric matrix and the discontinuous phase (fibers or fillers) and is considered to be the predominant factor that strongly affect the FRPCs performance.…”
Section: Frpcs and Componentsmentioning
confidence: 99%
“…minimize water uptake). 12 In this respect, Jagadish and Ray 21 have reported that the addition of natural pineapple leaves to epoxy resin, the mechanical properties were greatly enhanced. Vercher et al 22 have studied the influence of natural fiber types like rice husk and pine wood sawdust on the properties of polyvinyl chloride and polyethylene, respectively, to produce wood-plastic composites.…”
Section: Introductionmentioning
confidence: 99%
“…The surface modification of PLF helped to attain enhanced properties. Jagadish et al 10 investigated the characteristics of PLF/Epoxy composite by varying the fiber length, fiber loading, and composite thickness. The peak tensile and flexural strengths were achieved as 83.75 and 140.65 MPa at 5 mm thickness and 10% fiber loading.…”
Section: Introductionmentioning
confidence: 99%